Examen especial a la cartera de crédito de la cooperativa de ahorro y crédito El Comerciante Ltda., desde el 01 de octubre al 31 de diciembre 2015 - García Silva, Jhoana Patricia (2017)
Review applied to the Cooperative was concluded based on the fulfillment of important objectives: It was determined the reasonableness of the structure of the credit portfolio of the entity, by analyzing each of the accounts that make up this item; The compliance of the manager of the entity with the legal provisions, regulations, plans and other rules established for credit operations was verified by the application of interviews and questionnaires to said officers; As well as the accuracy of the internal records and transactions that support credit operations, through the use of techniques such as observation and inspection of documents, and finally the internal control of this area was evaluated, for which a questionnaire was applied Of internal control that allowed to have a clear vision of how the system of internal control in the Cooperative is being carried out. After completion of the work, it was determined that there is a concentration of functions in the Manager of the Cooperative, and a person should be hired immediately for the area of credit and collections, to act as a credit officer; Do not perform the home verification of debtors and guarantors in the credits dispatched, therefore it is recommended to check their place of room that allow in the later to locate them in case of delay of their loan installments; A printed document of the results of the credit bureau is not recorded in most files, the credit score must be printed to verify the risk concentration of those involved in the direct and indirect loans, so that the Cooperative does not increase its Risk of uncollectibility.